Do people save energy for agricultural production and produce more benefits through shift crop cultivation? – An energy balance analyses from paddy rice and upland crop production in Hau Giang province, Vietnam - Le Liem; Ngoc Nhan Pham; Thu Hien Nguyen (Acta Agriculturae Slovenica)
Agricultural energy analysis and better energy use efficiency will contribute to sustainable development adapt to climate change and ensure maintainable production. A case study from Hau Giang province agriculture energy was conducted on the comparison between the cultivation of paddy rice (PR) and upland crops, including corn, mungbean (MB), and black sesame (BS). The life cycle assessment methodology was used to estimate energy consumption and biomass energy production. Based on input-output energy inventoried results, the energy use efficiency, energy productivity, specific energy, and net energy were analysed. Selected crops require 39,501 – 59,638 MJ ha–1 crop–1 that is higher than energy providing for PR. Crop cultivation requires a large amount of energy from fossil fuels and electricity (12,946 – 34,375 MJ ha–1 crop–1). Biomass production achieves 779,670 MJ ha–1 crop–1 through corn cultivation, follow by rice farming (198,723 MJ ha–1 crop–1), BS and BS production (103,292 and 63,012 MJ ha–1 crop–1, respectively). Corn and PR reach the best energy analysis index because of their high biomass production. This study’s results underline the benefit of net energy from agricultural systems case study in Hau Giang province (19,380 – 720,032 MJ ha–1 crop–1).